A study on functional outcome following surgical fixation for lower spine injuries - Sivakumar, M.; Kumar, M. Ganesh (International Journal of Research in Orthopaedics, 2021)
Background: Cervical spine injuries are one of the common causes of serious morbidity mortality following trauma. 6% of trauma patients have spine injuries of which >50% is contributed by a cervical spine injury. The aim of the study was to determine the functional outcome following surgical fixation for sub-axial cervical spine. Methods: this prospective study involving 17 patients who were all admitted with sub-axial cervical spine injuries and amenable to intervention in our department of orthopedics and traumatology, government Theni medical college, Tamil Nadu, India in the year 2019-2020. Duration of 6 months from December 2019 to may 2020. Results: Most of the injuries presented within 24 hours of injury. Most of the patients presented with an incomplete neurological deficit. C5-C6 subluxation with disc bulge was the most common spinal injury. 5 patients were operated on more than 2 levels. The rest of the patients were operated on at 2 levels. Conclusions: We consider that the anterior decompression and fusion with a locking compression plate is a viable procedure in sub-axial cervical spine injuries.